The Strategies of Sustainable Watershed Management at Bedog Sub-Watershed, Special Region of Yogyakarta - Adhitama, S.Y.; Musthofa, A.; Rohmah, A.'A.; Nurwidiani, T.; Sejati, M.A.; Wati, E.T.; Saputro, R.; Rachmawati, R.; Nurjani, E.; Sudrajat, Sudrajat (Institute of Physics, 2022)
A watershed plays significant roles for maintaining the balance of ecosystem, particularly on the fluvial landform dynamics. Bedog Sub-Watershed as a part of Progo Watershed flows across 11 sub-districts from Sleman and Bantul Regency. This sub-watershed indicates rural-urban characteristics and multi-aspects problems, such as the loss of croplands, a massive land-use changes into built-up area, and the decrease of environmental carrying capacity. On the purposes of preventing the negative aftermaths, this research aimed to create the strategies of sustainable environmental management in case of Bedog Sub-Watershed. This research used secondary data from regional planning products, PODES data, and the relevant literature. Primary data was acquired from in-depth interview with BPDASHL Serayu-Opak-Progo and agricultural-related government agency to gain governmental perspective of watershed management. This research used qualitative descriptive technique to analyse the result of interview. Livelihood assets were calculated by scoring index. The SWOT and DPSIR analysis were conducted to create the relevant strategies implying physical, social-economy, and regional development perspectives in the post-COVID-19 pandemic. The strengthening of government's institutional aspects was the key to the management followed by necessary comprehensive study in Bedog Sub-Watershed management. © Published under licence by IOP Publishing Ltd.